Contribution to the development of product category rules for ceramic bricks - Almeida, Marisa Isabel (2017)
An Environmental Product Declaration (EPD) provides information on a product's environmental performance along its life cycle. This paper aims to contribute to the development of Product Category Rules (PCR) specific for ceramic bricks in order to support the establishment of a “cradle to grave” EPD. The methodology for developing the PCR takes into account ISO 14025, ISO 21930 and EN 15804, and the environmental profile is based on the Life Cycle Assessment (LCA) methodology. In this context, some core issues like product category definition, impact categories, indicators, cut-off criteria and allocation criteria are addressed. The selected impact categories for this study were: global warming, ozone layer depletion, photochemical oxidation, acidification, eutrophication, depletion of abiotic resources and respiratory inorganics. Indicators of energy and water consumption were also considered, as well as particle emissions to air. The results obtained from an LCA study on ceramic bricks produced in Portugal, to support the development of the PCR, show that the use of different fuels in the brick manufacturing stage has a significant effect in some impact categories. The use of petroleum coke generates higher impacts than natural gas or biomass. In general, the major environmental impacts occur in the brick manufacturing stage, mainly due to fuel usage in the firing operation. Particle emissions to air should be considered as an additional parameter in the EPD, being especially important when solid fuels are used. A sensitivity analysis of the cut-off criteria options was also conducted, which concluded that a 0.5% decrease in mass proved to be adequate for adoption, with a significant reduction in the effort required for data collection.